Criticality instruction for 6-year-olds in the Nordic educational context: A nexus of practice - Ivanov, Sergej (ASLA:s skriftserie, 2024)
Criticality is one of the UNESCO key competencies (Rieckmann, 2018) and itsinstruction to children is encouraged from a young age (e.g. Lai, 2011) as by theage of 4 they have necessary cognitive capacities (Schleihauf et al., 2022). Viewinginstruction as a nexus of practice (Scollon & Scollon, 2004), the aim of this articleis to trace how reported instances of criticality instruction for 6-year-olds arediscursively connected to the national policy of each Nordic country in the nexusof practice. In doing so, the article maps how the higher and lower scales(Blommaert, 2007) of criticality instruction intersect in the chosen nexus ofpractice (cf. Hult, 2010) by examining criticality (instruction) conceptions in thenational educational policy in each Nordic country and by identifying incidentsof scale jumping in regard to criticality (instruction) in the Nordic publishedempirical research. The collected data include the policy documents and peer-reviewed empirical studies from the Nordic early education context. The lownumber of empirical studies of criticality instruction for 6-year-olds has made itpossible to trace discursive connections across the scales in each national contextand shed light on criticality instruction as a nexus of practice.